Solidification performance of new trapezoidal longitudinal fins in latent heat thermal energy storage - Huang, Xinyu; Yao, Shouguang (Case studies in thermal engineering, 2021)
In order to improve the solidification performance of latent heat thermal energy storage system, a new trapezoidal longitudinal outer fin distributed by Fibonacci sequence is proposed due to the low thermal conductivity of phase change material. Firstly, the solidification behavior (temperature distribution, solid fraction, and solidification time) of three trapezoidal fins and traditional quadrilateral fin are compared by numerical simulation. The fin design with the highest improvement in solidification performance is selected and the dynamic temperature analysis is carried out. The Fibonacci sequence is introduced into the fin distribution and the effect of different longitudinal fin arrangements on solidification performance is analyzed. In addition, Response surface method is used to investigate the influence of geometric parameters of the trapezoidal fin based on Fibonacci sequence arrangement, and the optimal structure is obtained after optimization. The results show that the solidification time of phase change material after using modified trapezoidal fin with Fibonacci sequence is shortened by 45.28% compared with the traditional quadrilateral fin. Finally, the temperature difference between the inner tube cold fluid and the phase change material is greater than 20 K, which can ensure the excellent solidification performance.